Technology policy fitting concept with reality - Kash, Don E.
We have crossed a historical Rubicon into an era in which the capacity to innovate technology complex technologies has created a set of opportunities and problems that make our reductionist and simplistic linear models of policy and governance obsolete. America must base its technology policy on a synthesis of both international experience and new conceptualizations. The most important recent experience with successful technological innovation has taken place in Asia, whereas the most rapid conceptual advances appear to be occuring in Europe and the U.S. Complexity is the key factor in both.